EFFECT OF FLOUR AND PAPAYA LEAF EXTRACT (Carica papaya L.) ADDITION TO FEED ON GAS PRODUCTION, DIGESTIBILITY AND ENERGY VALUES IN VITRO - Miftahul Khoiriyah; Siti Chuzaemi; Herni Sudarwati (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2016)
The purpose of this research was to analyze the effect of papaya (Carica papaya L) leaf extract and flour on a mixed feed made from elephant grass (Pennisetum purpureum) and pollard(Triticum aestivum) on gas production, in vitro digestibility dry matter (DDM), digestibility organic matter (DOM), and the value of energy. The materials used in this research was mixed feed consisting of grass, pollard and papaya leafs as feed supplement. The method used is a Randomized Block Design with 5 treatments and 3 replications. P0 was control feed, P1 was P0 + 2% of papaya leaf flour, P2 was P0 + 4% of papaya leaf flour, P3 was P0 + 2% papaya leaf extract, and P4 was P0 + 4% papaya leaf extract. Duncan's Multiple Range Test was carried out if there found any difference in treatments. The result of the research shows that papaya leaf extract and flour did not give significant influence (P> 0,05) for gas production, in vitro digestibility dry matter and digestibility organic matter , and energy value , but gave significant influence (P <0,01) for net energy. The addition of 4% papaya leaf extract gave the best results for gas production value (value b = 133,16 ml/500 mgDM and value c=0,064 ml/h), digestibility dry matter and digestibility organic value (DDM = 63,57 % and DOM = 65,49 %), metabolizable energy 8,47 MJ/KgDM value and net energy 6,29 MJ/KgDM value. Those can be concluded that addition of 2% and 4% papaya leaf extract and papaya flour can’t increase gas production, in vitro digestibility of dry matter and organic matter but increases net energy value. Suggestions from this research was that feeding a mixture of grass and pollard added with 4% of papaya leaf flour should be conducted to determine the level of productivity. Keywords : Papaya leaf, gas production, in vitro digestibility, energy